Reconstruction of maxillectomy and midfacial defects using latissimus dorsi-scapular free flaps in a comprehensive cancer center. (December 2019) - Moya-Plana, A.; Veyrat, M.; Honart, J.F.; de Fremicourt, K.; Alkhashnam, H.; Sarfati, B.; Janot, F.; Leymarie, N.; Temam, S.; Kolb, F.
Highlights: An accurate classification of midfacial defects is mandatory. Latissimus dorsi-scapular free flap is reliable for midface reconstruction. Primary reconstruction is feasible with acceptable outcomes. More than 90% of the patients had no postoperative functional disorders. Soft palate involvement is a prognostic factor of speech and swallowing disorders. Abstract: Background: The standard of care for sinonasal malignancies is a large surgical resection followed by radiotherapy. Midfacial defects resulting from maxillectomy require a complex reconstruction procedure. Given their adaptability, chimeric flaps such as latissimus dorsi-scapular (LDS) free flaps appear to be a good option. Material & methods: We performed a single-center retrospective study of consecutive patients with sinonasal cancers where a LDS free flap was used for reconstruction. We assessed the postoperative complications and the functional, aesthetic and oncologic outcomes. Results: Eighty-four patients were included. Primary tumors were staged as T4a in 68% of cases; 38.3% of the patients received induction chemotherapy and 82.7% received adjuvant radiotherapy. Based on our classification of midfacial and palatal defects, the majority of the patients (69%) had a type IIa with interruption of the three facial pillars. The orbital floor was removed in 55.9% of cases. The median follow-up was 45 months. Total flap necrosis with no possible revascularization occurred in 5.9% of cases. For the orbital reconstruction, a revision procedure was needed for necrosis and/or infection of the costal cartilage graft in eight cases (17%). More than 90% of the patients had no functional disorders regarding speaking, swallowing and chewing. Soft palate involvement was a prognostic factor of speech (p < 10 −4 ) and swallowing (p = .005) disorders. Dental rehabilitation was realized in 70.2% of the patients. No severe complications were observed in the donor site, except for one seroma. Conclusion: A LDS free flap is a reliable technique for the reconstruction of complex midfacial defects.